UPAYA PENINGKATAN EKONOMI MASYARAKAT MELALUI PELATIHAN DAN PENGOLAHAN PRODUK SALAD BUAH - Amelya Yuniar (Politeknik Negeri Sriwijaya, 2022)
Community service on the topic of entrepreneurship is a community service activity that involves students as participants and lecturers as supervisors that focus on entrepreneurial themes or activities. This community service activity is carried out to provide training and processing of fruit salad products in improving the economy of the Lubuk Enau community. This research method uses qualitative research. The result of this series of community service activities is the development of fruit salad food products with more modern and online-based packaging and marketing such as Facebook, WhatsApp, and Instagram. It is hoped that after this service program is carried out, the people who take part in this training can have broad knowledge and insight and dare to continue to innovate and increase creativity in order to improve their standard of living for the better.